Machaerium hirtum (Vell.) stellfeld alleviates acute pain and inflammation: Potential mechanisms of action - Agostinho Lopes, Juliana [UNESP]; Peixoto Rodrigues, Vinícius [UNESP]; Marucci Pereira Tangerina, Marcelo [UNESP]; Machado Da Rocha, Lucia Regina [UNESP]; Massucato Nishijima, Catarine; Alfieri Nunes, Vania Vasti [UNESP]; Rolim De Almeida, Luiz Fernando [UNESP]; Vilegas, Wagner [UNESP]; Soares Dos Santos, Adair Roberto; Sannomiya, Miriam; Hiruma-Lima, Clélia Akiko [UNESP] (MDPI, 2020)
Machaerium hirtum (Vell.) Stellfeld (Fabaceae) known in Brazil as “jacaranda de espinho” or “espinheira santa nativa” is a medicinal plant commonly used in folk medicine to treat ulcers, cough and diarrhea. This study aimed to investigate the anti-inflammatory and antinociceptive effects of hydroalcoholic extracts from M. hirtum twig (HEMh) using in vivo experimental models of nociception through the involvement of transient receptor potential channels, acid-sensing ion channel (ASIC), nitrergic, opioidergic, glutamatergic, and supraspinal pathways. Our results revealed an antinociceptive effect of HEMh mediated by the opioidergic, L-arginine-nitric oxide and glutamate systems, as well as by interactions with TRPA1/ASIC channels. The anti-inflammatory effect of HEMh evaluated with a xylene-induced ear edema and by the involvement of arachidonic acid and prostaglandin E2 (PGE2) showed involvement of the COX pathway, based on observed decreases in PGE2 levels. A phytochemical investigation of the HEMh led to the isolation of α- amyrin, β-amyrin, allantoin, apigenin-7-methoxy-6-C-β-D-glucopyranoside, and apigenin-6-C-β-Dglucopyranosyl- 8-C-β-D-xylopyranoside. In conclusion, the acute oral administration of HEMh inhibits the nociceptive behavioral response in animals through the nitrergic, opioid, glutamatergic pathways, and by inhibition of the TRPA1 and ASIC channels, without causing locomotor dysfunction. In addition, its anti-inflammatory effect is associated with the COX pathway and decreased PGE2 levels.
Keywords: Anti-inflammatory action; Antinociceptive effect; Machaerium hirtum